(untitled) (Docentes 2.0 Journal, 2024)
Public policies in education and teaching performance are crucial in building the foundations that promote students’ well-being and educational development at their different academic levels. The research aimed to analyze the link between public policies and teaching performance. It was based on the hypothetico-deductive method and positivist paradigm, with a quantitative approach, non-experimental design, correlational type, and cross-sectional. The sample included 114 teachers from public educational institutions, evaluated using the "Educational Policy Measurement Scale" and the "Knowledge Test on the Framework of Good Teaching Performance." The results revealed the absence of a significant contribution between public educational policies and teaching performance in the analyzed sample (r = -0.008, p = 0.931). Despite the lack of qualification, the study contributes to the educational field by delving into the complexity of this interaction. Therefore, the discussion highlights the need to consider various factors and examine these relationships in specific contexts. Finally, the work discovered a solid foundation for future research, suggesting the exploration of underlying factors and new dimensions in this relationship.